First avoidance, then engagement: Political parties' issue competition in the electoral cycle. (March 2022) - Seeberg, Henrik Bech
A major contradiction in party research is between the saliency theory and the logic of issue convergence, or what is often referred to as issue avoidance vs. engagement. Extant research shows that parties both emphasize only their own issues and engage each other's issues. This study addresses this contradiction and argues that both perspectives have merits. The key to unlocking the puzzle is to unwind the electoral cycle. As far as possible into the electoral cycle, parties apply a long-term strategy and talk past each other. Yet, as the election draws closer, parties realize that they cannot change the agenda and therefore switch to a short-term strategy to engage rival parties' issues. This argument is tested across multiple issues on a new dataset consisting of 19, 350 press releases issued by the political parties in Denmark during several election cycles, 2004–2019.